The modern Latin American city: end of the XIX century-1920: An approach to social segregation through the urbanism of the elites - Zhingre, Raúl (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This work studies the history of the modern city from the end of the 19th century to 1920, in which the educated and hygienic city stands out. In this way, the city was linked to the policies of planning, hygiene, decoration, religious celebrations, commemorations and beautification meetings. This served to promote the modern city at the service of the elite, to the interests of building national memories and modernizing the republics. Streets, parks and buildings were inaugurated, a situation that allowed a modern city scenario, but free of impoverished segments, for which the social control of urban public space was proposed.